The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1111/epi.16536
|View full text |Cite
|
Sign up to set email alerts
|

A rat model of valproate teratogenicity from chronic oral treatment during pregnancy

Abstract: Objective: Sodium valproate (VPA), the most effective antiepileptic drug for patients with genetic generalized epilepsy (GGE), is a potent human teratogen that increases the risk of a range of congenital malformations, including spina bifida. The mechanisms underlying this teratogenicity are not known, but may involve genetic risk factors. This study aimed to develop an animal model of VPA-induced birth defects. Methods: We used three different rat strains: inbred Genetic Absence Epilepsy Rats From Strasbourg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Animals assigned to the chronic group were treated with a feed containing 20 g/kg valproate (see Methods and Jazayeri et al ., 2020 ) for at least 3 weeks for non-pregnant adults, and at least 2 weeks prior to mating followed by a further 19 days for E19 experiments and 25–26 days for P4 experiments. They were compared with animals fed chronically with food not containing valproate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Animals assigned to the chronic group were treated with a feed containing 20 g/kg valproate (see Methods and Jazayeri et al ., 2020 ) for at least 3 weeks for non-pregnant adults, and at least 2 weeks prior to mating followed by a further 19 days for E19 experiments and 25–26 days for P4 experiments. They were compared with animals fed chronically with food not containing valproate.…”
Section: Resultsmentioning
confidence: 99%
“…The chronic treatment used in the present study was that developed by Jazayeri et al . (2020) who showed that a feed containing 20 g/kg valproate resulted in blood levels in pregnant rats similar to those in pregnant mothers on treatment with this antiepileptic drug.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations